Contributions of inwardly rectifying K+ currents to repolarization assessed using mathematical models of human ventricular myocytes. - Fink, M; Giles, W; Noble, D (2006)
Repolarization of the action potential (AP) in cardiac muscle is a major determinant of refractoriness and excitability, and can also strongly modulate excitation-contraction coupling. In clinical cardiac electrophysiology, the Q-T interval, and hence action potential duration, is both an essential marker of normal function and an indicator of risk for arrhythmic events. It is now well known that the termination of the plateau phase of the AP and the repolarization waveform involve a complex interaction of transmembrane ionic currents. These include a slowly inactivating Na+ current, inactivating Ca2+ current, the decline of an electrogenic current due to Na+/Ca2+ exchange and activation of three or four different K+ currents. At present, many of the quantitative aspects of this important physiological and pathophysiological process remain incompletely understood. Recently, three mathematical models of the membrane AP in human ventricle myocyte have been developed and made available on the Internet. In this study, we have implemented these models for the purpose of comparing the K+ currents, which are responsible for terminating the plateau phase of the AP and generating its repolarization. In this paper, our emphasis is on the two highly nonlinear inwardly rectifying potassium currents, (IK1) and (IK,r). A more general goal is to obtain improved understanding of the ionic mechanisms, which underlie all-or-none repolarization and the parameter denoted 'repolarization reserve' in the human ventricle. Further, insights into these fundamental variables can be expected to provide a more rational basis for clinical assessment of the Q-T and Q-TC intervals, and hence provide insights into some of the very substantial efforts in safety pharmacology, which are based on these parameters.